A corridors and power-oriented perspective on energy-service demand and needs satisfaction. Issue 1 (1st January 2021) - Fuchs, Doris; Steinberger, Julia; Pirgmaier, Elke; Lamb, William; Brand-Correa, Lina; Mattioli, Giulio; Cullen, Jonathan
Abstract: In this article, we explore the concept of consumption corridors as it might apply to energy use, with specific attention to both wellbeing and power relations. We employ the distinction between energy provisioning and human-need satisfaction to explore different configurations of energy use, as well as their possible dynamics. Specifically, we draw on past research documenting the benefits of decoupling our thinking about energy services and needs satisfaction and use it as a basis to identify scenarios characterized by different degrees of access to energy services and levels of resource demand. We then translate this perspective to the logic of sustainable consumption corridors. We delineate how minimum and maximum consumption standards would relate to combinations of energy-service demand and needs-satisfier access. Finally, we explore how power dynamics, specifically exercises of discursive power, might move societal trajectories toward sustainable combinations of energy provisioning and needs satisfaction or away from them.